9x-3=4x+18

Simple and best practice solution for 9x-3=4x+18 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9x-3=4x+18 equation:


Simplifying
9x + -3 = 4x + 18

Reorder the terms:
-3 + 9x = 4x + 18

Reorder the terms:
-3 + 9x = 18 + 4x

Solving
-3 + 9x = 18 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
-3 + 9x + -4x = 18 + 4x + -4x

Combine like terms: 9x + -4x = 5x
-3 + 5x = 18 + 4x + -4x

Combine like terms: 4x + -4x = 0
-3 + 5x = 18 + 0
-3 + 5x = 18

Add '3' to each side of the equation.
-3 + 3 + 5x = 18 + 3

Combine like terms: -3 + 3 = 0
0 + 5x = 18 + 3
5x = 18 + 3

Combine like terms: 18 + 3 = 21
5x = 21

Divide each side by '5'.
x = 4.2

Simplifying
x = 4.2

See similar equations:

| 8+2*5=m | | (-7)+(-9)= | | 3y^3+4y^2-6x-8=0 | | 7(x-4)=12 | | f(x)=ln(x^2-5*x+6) | | 4(b-6)=6 | | fx=8cos(-x/4) | | 10+5y=4 | | 7(1/2)*x=7/8 | | 7(1/2)^x=7/8 | | 8x-15=5x-12 | | -x-2=-4x+7 | | q+2=6q | | 6q+0(1-q)= | | 2(3a+6)=4(3-7a)+6a | | f(x)=5e^2x-e | | 3q+2(1-q)= | | 6x+16=10x+44 | | 1.6(x-3)=-80 | | .6*x+4=7 | | 4x-13-6x+4=3-9X-7+3x | | 8x-2=4y | | A=p+petfory | | x+(2x+1)=-2 | | 0.4t-0.3=1.8-0.1(2t+9) | | 4x^3-2x^2+3=0 | | 3(y-3)-2=7 | | 2x+2y=81 | | 2n/4n | | 4(a-3)=6a+11 | | 4a-3=6a+11 | | (4a-3)+(6a+11)= |

Equations solver categories